Serviceability and ductility behaviour of hybrid reinforced concrete beams partially composed of engineered cementitious composite (ECC) - Ahmed A. Radwan; Ahmed Ghallab; Ahmed M. Farghal Maree (Scientific Reports)
Abstract GFRP bars can be used partially or fully instead of steel bars in RC-beams to eliminate corrosion problems, especially in harsh environments. Also, the implementation of the combined use of engineered cementitious composite (ECC) and the hybrid (steel-GFRP) reinforcement in concrete beams can enhance strength and serviceability. In this paper, seven beams; one as a control beam cast with traditional concrete, and six partial ECC RC-beams with GFRP bars only or RC-hybrid (steel-GFRP) bars were designed to investigate both deflection and ductility behaviour of such beam type. This research explored reinforcement types and two ECC configurations: (a) a bottom layer of varying thickness, (b) a U-shaped formwork. All specimens underwent four-point bending testing to examine cracks distribution, moment-strain, and moment-curvature relation, in addition to the evaluation of deflection equations and assessment of ductility of the composite beams. The experimental findings revealed that thicker ECC in the tension zone led to changes in the distribution of vertical cracks, stiffness, and energy absorption. The use of U-shaped ECC configuration generally leads to an increase in the ductility index. A specific construction technique with a corrugated surface was implemented, which created a roughened surface, improved the interface shear transfer, and eliminated bond failure at the interface. The deflection values calculated using ACI 318 -19 and CSA S806-12 equations showed good correlation with the experimentally measured deflections. In contrast, the ACI 440.1R-15 equations did not accurately capture the deflection behavior across all tested specimens.